2023
DOI: 10.3390/biology12091163
|View full text |Cite
|
Sign up to set email alerts
|

A Story of Kinases and Adaptors: The Role of Lck, ZAP-70 and LAT in Switch Panel Governing T-Cell Development and Activation

Luis M. Fernández-Aguilar,
Inmaculada Vico-Barranco,
Mikel M. Arbulo-Echevarria
et al.

Abstract: Specific antigen recognition is one of the immune system’s features that allows it to mount intense yet controlled responses to an infinity of potential threats. T cells play a relevant role in the host defense and the clearance of pathogens by means of the specific recognition of peptide antigens presented by antigen-presenting cells (APCs), and, to do so, they are equipped with a clonally distributed antigen receptor called the T-cell receptor (TCR). Upon the specific engagement of the TCR, multiple intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 144 publications
0
1
0
Order By: Relevance
“…Full ZAP70 activation thereafter phosphorylates the critical adaptors LAT at tyrosine residues including Y191 to coordinate the downstream signaling cascade. 1,37,47 Our protein analysis revealed that the activating phosphorylations of LCK, ZAP70, and LAT in T-ALL cells were consistently abolished after treatment with a low concentration of 1232030-35-1, indicating an overall inhibited state of pre-TCR-LCK signaling. This resulted in not only robust in vitro antiproliferation effects in T-ALL cells, but also promising therapeutic effects in T-ALL mice.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Full ZAP70 activation thereafter phosphorylates the critical adaptors LAT at tyrosine residues including Y191 to coordinate the downstream signaling cascade. 1,37,47 Our protein analysis revealed that the activating phosphorylations of LCK, ZAP70, and LAT in T-ALL cells were consistently abolished after treatment with a low concentration of 1232030-35-1, indicating an overall inhibited state of pre-TCR-LCK signaling. This resulted in not only robust in vitro antiproliferation effects in T-ALL cells, but also promising therapeutic effects in T-ALL mice.…”
Section: Discussionmentioning
confidence: 82%
“…Previous reports indicated that the phosphorylation of LCK at Y394 is essential for its activation. 47 Upon TCR stimulation, LCK phosphorylates the immunoreceptor tyrosine-based activation motif (ITAM) within the TCR, which leads to sequential ZAP70 phosphorylation at Y319 and Y493. Full ZAP70 activation thereafter phosphorylates the critical adaptors LAT at tyrosine residues including Y191 to coordinate the downstream signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This regulation of lck activity is crucial for recognizing foreign antigens without attacking non-foreign tissues, thereby maintaining immune tolerance. Zeta-chainassociated protein kinase 70 (zap-70), a critical tyrosine kinase in the T cell receptor (TCR) signaling pathway, operates alongside lck in the early events of TCR signaling, ultimately activating T cells [39]. Furthermore, zap-70 is involved in regulating the immune response of T cells by controlling the intensity and timing of signaling, ensuring appropriate immune responses and avoiding immunopathological processes due to overactivation [40].…”
Section: Discussionmentioning
confidence: 99%